Remarkable increase in triboelectrification by enhancing the conformable contact and adhesion energy with a film-covered pillar structure. (April 2017) - Lee, Ju Hyun; Yu, Insang; Hyun, Seung; Kim, Jin Kon; Jeong, Unyong
Abstract: Structural modification of the surface has been widely investigated in triboelectric energy generation to improve the power harvested. Large contact area, large surface area and good dielectric performance are the basic design principles needed for the structures, while energy harvesting from low-energy mechanical motions is desirable. This work suggests that a film-covered pillar structure made of polydimethylsiloxane (PDMS) improved its output performance by satisfying all the basic design parameters, especially, the conformable contact and easy deformation. The contact area and the adhesion energy of the film-covered pillar structure are quantitatively compared with those from the flat PDMS substrates and the pillar-only structures. We report that the film-covered pillar structure remarkably enhances the charge generation and increases the output voltage and the current density. We also emphasize the optimized thickness of the cover film for triboelectric performance. The triboelectric power generator operating by low-energy mechanical motions like a gentle finger-touch has been demonstrated as a possibility for human-based energy harvesting device in the future. Graphical abstract: Highlights: The film-covered pillar structure enhances the conformal contact and adhesion. The thin cover film increases the triboelectric charge generation and the output. The triboelectric devices operate by low-energy motions like gentle finger-touch. We discuss quantitatively on the adhesion energy as a triboelectric design parameter.